Rancang Bangun Prototipe Insenerator Untuk Sampah Rumah Sakit Dengan Teknologi Pengendalian Polusi Udara - Suryanto Suryanto; Musrady Mulyadi; Ummy Kalsum Mustam; Medi Adeyanto Sapan (Jurnal Sinergi Jurusan Teknik Mesin, 2022)
Medical waste has become a major problem today in Indonesia because of the COVID-19 pandemic which has resulted in many hospitals being full of patients, resulting in an increase in medical waste. Handling of waste that is carried out is still not appropriate so that waste accumulates in garbage collection sites and in final disposal sites. As a result, the waste becomes a means of germs, bacteria, and animals that can spread disease to the surrounding environment. One way that is often used is to burn waste to reduce its volume. The incinerator is a modern means of burning waste by using a combustion system up to a temperature of 1000°C and can reduce the volume of waste by up to 90%. The research method used in making the design of the incinerator is starting from the design of the combustion chamber, the manufacturing and assembly stages, until testing is carried out on the tool. The test results from the incinerator can accommodate as much as 5kg to 10kg of waste with a combustion chamber volume of 0.165 m3. The highest temperature of the incinerator is at minute 15 with a temperature reaching 270.6°C, while the lowest temperature is at minute 150 with a temperature of 42.5°C.